2017
DOI: 10.1186/s12913-016-1969-2
|View full text |Cite
|
Sign up to set email alerts
|

Availability of essential medicines in selected public, primary and secondary health care institutions of a rural Sri Lankan district: a spot survey

Abstract: BackgroundAssessment of the availability of essential medicines, in rural areas of countries with free state health care system, is scarce. Dependence on essential medicines among the population in rural sector is considered to be high. Assessing the availability of essential medicines in selected state owned primary and secondary health care institutions of a rural district will help to identify areas where improvement is needed.MethodsA descriptive cross sectional study, covering selected five primary and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Expense is still a concern among patients who receive medications at universal-free pharmacies. A recent study revealed inadequacies in the availability of essential medicines at universal-free healthcare institutions of Anuradhapura [37]. Therefore, there might be an instance when the patient is expected to purchase part of the prescription from a fee-levying pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…Expense is still a concern among patients who receive medications at universal-free pharmacies. A recent study revealed inadequacies in the availability of essential medicines at universal-free healthcare institutions of Anuradhapura [37]. Therefore, there might be an instance when the patient is expected to purchase part of the prescription from a fee-levying pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…WHO recommends that ideally the availability of 80% or more must be considered optimal for the Essential Medicines (EMs) ( WHO, 2015 ). We described the availability of medicines according to the following criteria, used by many WHO/HAI surveys: <30%: very low, 30–49%: low, 50–80%: fairly high, and >80%: high ( Rathish et al, 2017 ; Saeed et al, 2019 ). Associations between availability and other variables were analyzed using the binary logistic regression (available = 1, unavailable = 0).…”
Section: Methodsologymentioning
confidence: 99%
“…The people who most often embodied the status of navigators were Community Health Workers (CHWs) ( n = 16) ( Behforouz et al , 2004 ; Koenig et al , 2004 ; Mukherjee et al , 2006 ; Mukherjee and Eustache, 2007 ; Penny et al , 2007 ; Guinhouya et al , 2010 ; Ivers et al , 2011 ; Rich et al , 2012 ; Franke et al , 2013 ; Mugeni et al , 2014 ; Gupta et al , 2016 ; Reif et al , 2016 ; Ferrand et al , 2017 ; Matousek et al , 2017 ; Busza et al , 2018 ; Gignoux et al , 2018 ; Munyaneza et al , 2018 ; Rogers et al , 2018 ; van Diessen et al , 2018 ; Wroe et al , 2018 ), also known in Uganda as village health teams (VHTs) ( Altaras et al , 2017 ; Ekirapa-Kiracho et al , 2017 ; Musinguzi et al , 2017 ). Other individuals ( n = 13) were also implicated in navigation programmes, such as community own resource persons ( Kema et al , 2012 ), community health agents (CHAs) ( Savoie and Lambert, 2012 ), community cadres ( Patel et al , 2012 ), female community health volunteers (FCHVs) ( Andersen et al , 2013 ; Panday et al , 2017 ; Neupane et al , 2018 ), peer HIV educators ( Vu et al , 2017 ), peers (members of the community) ( Muzyamba, 2019 ), community-based rehabilitation workers ( Asher et al , 2018 ), lay counsellors ( Barnabas et al , 2016 ; Ware et al , 2016 ), community motivators ( Kandeh et al , 1997 ), community volunteers ( Seim et al , 2014 ) and community rela...…”
Section: Resultsmentioning
confidence: 99%